Elsa Cross. 2022. El Lejano Oriente en la poesía mexicana. Ciudad de México: Universidad Nacional Autónoma de México. 824 pp. ISBN 9786073070201 - Mata Sandoval, Rodolfo (Estudios de Asia y África, 2024)
Elsa Cross. 2022. El Lejano Oriente en la poesía mexicana. Ciudad de México: Universidad Nacional Autónoma de México. 824 pp. ISBN 9786073070201